Pug's snow day - May, Kyla (May, Kyla. Diary of a pug, 2020)
Bub the pug has never seen snow before, and when Duchess the cat tells him it is frozen rain he is appalled and does not want to go out even to play with his human, Bella--but the week is about to get worse because a new family has moved in next door, and they apparently have a pet monster (at least if Nutz the squirrel can be believed) and Bella's mother has arranged a play date for Sunday.